2022
DOI: 10.1007/s11661-022-06680-8
|View full text |Cite
|
Sign up to set email alerts
|

On the Rate Dependence of Precipitate Formation and Dissolution in a Nickel-Base Superalloy

Abstract: The temporal dependence of $$\gamma '$$ γ ′ dissolution in the polycrystalline Ni-base superalloy RR1000 has been studied with implications to thermo-mechanical processing. A resistivity-based method using an electro-thermal mechanical testing (ETMT), which overcomes the drawbacks associated with other approaches, such as calorimetry, dilatometry, and diffraction, has been used to explore the effect of transient and isothermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…[18][19][20][21] In the case of Ni-based superalloys, it can be used to characterize grain growth, [22] volume fraction of the c¢ phase, [23,24] and dissolution and precipitation kinetics of c¢ phase. [24,25] However, electrical current can accelerate recovery and recrystallization, and it can, in principle, affect the phase transformation process in metallic materials. [26][27][28] Several studies have made attempts to extract microstructural information from Ni-based superalloys through electrical resistivity measurement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20][21] In the case of Ni-based superalloys, it can be used to characterize grain growth, [22] volume fraction of the c¢ phase, [23,24] and dissolution and precipitation kinetics of c¢ phase. [24,25] However, electrical current can accelerate recovery and recrystallization, and it can, in principle, affect the phase transformation process in metallic materials. [26][27][28] Several studies have made attempts to extract microstructural information from Ni-based superalloys through electrical resistivity measurement.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] Several studies have made attempts to extract microstructural information from Ni-based superalloys through electrical resistivity measurement. [22,23,25,[29][30][31][32][33] Other studies directly compared DSC and resistivity for analyses of physical properties, but data on superalloys are particularly limited. [19][20][21]34,35] Overall, the analyses so far have been limited to specific and fundamental uses, and there is a need for comprehensive understanding to make the best use of this method.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, it has been observed that precipitate coarsening at sub-solvus temperatures leads to decreasing resistance, owing to a reduction in c/c¢ interfacial area resulting in reduced electron scattering at interfacial sites. [18] A more potent case exists in the case of additively built microstructures, where precipitate sizes of the order of ~5 nm [29] result in a markedly higher resistivity (~100 to 150 nXm) in the as-built condition, compared with the case where the re-precipitated c¢ following heat treatment is characterized by a precipitate size of ~100 nm. [30] However, this effect can be negated in the present experiments, since the isothermal hold is above the local solvus, as indicated by the normalized resistance curve, as in Figures 3 and 12.…”
Section: Discussionmentioning
confidence: 99%
“…Electrothermal mechanical testing (ETMT) is a technique developed at the National Physical Laboratory (NPL) capable of measuring a wide range of mechanical and physical properties in miniature test specimens. [17][18][19][20] The ETMT equipment used for these experiments is fitted with a ± 0.5 kN load cell and provides resistance heating to test specimens via direct current (DC) across the specimen. Temperature is controlled via a Type-R Pt/Pt-13 pct Rh thermocouple spot welded along the center of the gage length ~(2.75 to 3 mm) where the temperature is uniform within ± 1 K. [17] Resistance changes are measured between two Pt/ Pt-13 pct Rh wires attached within the isothermal gage length of the specimen.…”
Section: B Electrothermal Mechanical Testing (Etmt)mentioning
confidence: 99%
See 1 more Smart Citation